Nature of manganese species in Ce1-xMnxO2-delta solid solutions synthesized by the solution combustion route - Murugan, B.; Ramaswamy, A. V.; Srinivas, D.; Gopinath, Chinnakonda S.; Ramaswamy, V. (Chemistry of Materials, 2005)
A series of manganese-cerium oxide composites with Mn concentrations in the range of 1-20 mol % in ceria was prepared by the solution combustion technique using urea as fuel. The nature, type, and oxidation state of Mn species in ceria were investigated by X-ray diffraction (XRD), diffuse reflectance UV-visible spectroscopy, electron paramagnetic resonance (EPR), X-ray photoelectron spectroscopy, and temperature-programmed reduction techniques. The study reveals that the method of preparation significantly influences the type of manganese species in ceria. Wet-impregnation, coprecipitation, and solid-state synthesis techniques lead to clustered MnOx-like species in the ceria matrix, while the present method of preparation (solution combustion route) yields a highly dispersed form of Mn species. In the reported series of samples, Mn is present mainly in +2 and +3 oxidation states and there is no evidence for the presence of Mn 41 species. Powder X-ray diffraction studies at variable temperatures (298-1323 K) indicate the formation of Ce1-xMnxO2-delta Solid solutions. No separate MnOx-type phase was detected even at 1323 K. EPR studies reveal that the isolated Mn2+ and Mn2+ species are present in at least three different structural locations: species A, Mn ions in ceria-lattice defect sites; species B, Mn ions in framework Ce4+ locations; and species C, Mn ions in interstitial locations and at the surface of ceria. The Mn3+ ions in ceria exhibit a facile reduction and reoxidation behavior when exposed to dry hydrogen and subsequently to air at elevated. temperatures. A highly dispersed state of Mn3+ and Mn2+ in ceria, facile redox behavior, and a synergistic Mn-ceria interaction are some of the unique properties of this material prepared by the solution combustion procedure.

Negative thermal expansion in silicalite-1 and zirconium silicalite-1 having MFI structure - Bhange, Deu S.; Ramaswamy, V. (Materials Research Bulletin, 2006)
In situ high temperature X-ray diffraction (HTXRD) studies on monoclinic silicalite-1 (S-1, silica polymorph of ZSM-5) and an orthorhombic metallosilicate molecular sieve, zirconium silicalite-1 (ZrS-1) with MFI structure (Si/Zr = 50) have been carried out using a laboratory X-ray diffractometer with an Anton Parr HTK 1600 attachment. While the structure of the S-I collapsed at 1123 K forming alpha-cristobalite. S-1 and ZrS-1 showed a complex thermal expansion behavior in the temperature range 298-1023 K, ZrS-1 was stable. Powder X-ray diffraction (PXRD) data taken in this region have shown strong negative lattice thermal expansion coefficient, alpha(v) = -6.75 x 10(-6) and - 17.92 x 10(-6) K-1 in the temperature range 298-1023 K-1 for S-1 and ZrS-1 samples, respectively. The thermal expansion behavior of S-1 and ZrS-1 is anisotropic, with the relative strength of contraction along a axis is more than that along b and c axes. Three different thermal expansion regions could be identified in the overall temperature range (298-1023 K) studied, corroborating with the three steps of weight loss in the TG curve of ZrS-1 sample. While the region between 298 and 423 K, displays positive thermal expansion coefficient with alpha(v) = 2.647 x 10(-6) and 4.24 x 10(-6) K-1, the second region between 423 and 873 K shows strong negative thermal expansion (NTE) coefficient alpha(v) = -7.602 x 10(-6) and - 15.04 x 10(-6) K-1, respectively, for S-1 and ZrS-1 samples. The region between 873 and 1023 K, shows a very strong NTE coefficient with alpha(v) = - 12.08 x 10(-6) and -45.622 x 10(-6) K-1 for S-1 and ZrS-1, respectively, which is the highest in the whole temperature range studied. NTE seen over a temperature range 298-1023 K could be associated with transverse vibrations of bridging oxygen atoms in the structure which results in an apparent shortening of the Si-O distances. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: microporous materials; phase transitions; Thermal expansion; X-ray diffraction

Selective oxidation of ethane over Mo-V-Al-O oxide catalysts: insight to the factors affecting the selectivity of ethylene and acetic acid and structure-activity correlation studies - Sankaranarayanan, T. M.; Ingle, Rohit H.; Gaikwad, T. B.; Lokhande, S. K.; Raja, T.; Devi, R. N.; Ramaswamy, V.; Manikandan, Palanichamy (Catalysis Letters, 2008)
Catalysts of general formula, MoVAlOx were prepared with the initial elemental composition of 1:0.34:0.167 (Mo:V:Al) at a pH value in the range of 1-4. The elemental analysis showed that the final composition of the catalysts is pH dependant. The performance of the catalysts was tested for selective oxidation of ethane to give ethylene and acetic acid. While all of them were active for ethane oxidation with a moderate conversion, the catalyst prepared at pH 2 showed a highest activity with 23% ethane conversion and a combined selectivity of 80.6% to ethylene and acetic acid. The catalyst prepared at pH 4 was least selective to ethylene and acetic acid. Various techniques like powder XRD, SEM, Raman, UV-Vis and EPR were used to characterize the catalysts and to identify the active phases responsible for the selective oxidation of ethane. The powder XRD data showed that the catalysts prepared at pH 1 and 2 contain mainly of MoO3 and MoV2O8 along with traces of Mo4O11. The amount of MoO3 was slightly higher in the catalyst prepared at pH 1. However, the catalyst prepared at pH 3 contains mainly of MoV2O8 with no trace of MoO3. The catalyst prepared at pH 4 showed V2O5 as the major phase along with MoVAlO4 phase. The Raman data corroborated the XRD results. EPR and UV-Vis studies indicated the presence of traces of V-4 in pH 1 and 2 catalysts and significant amount of Mo5+ in all the catalysts. Thus, the high activity and selectivity to ethylene and acetic acid are attributed to the presence of MoV2O8 phase and other reduced species like Mo4O11 phase supported on MoO3. The presence of V and Mo ions in a partially reduced form seems to play a crucial role in the selective oxidation of ethane.
Keywords: Acetic acid; ethane; Ethylene; mixed metal oxide; Selective oxidation